Optimisation of electrical discharge machining process with CuW powder metallurgy electrode using grey relation theory. (1st January 2011) - Beri, Naveen; Kumar, Anil; Maheshwari, S.; Sharma, C.
In this paper, an attempt has been made to correlate the usefulness of powder metallurgy (PM) electrodes in electrical discharge machining (EDM). This paper explains the same with the help of experimentation on AISID2 steel in kerosene with CuW (25% Cu and 75% W) PM electrode. An L18 orthogonal array was used to identify the effect of process parameters (viz. electrode material, duty cycle, flushing pressure and current) on the performance characteristics i.e., material removal rate surface roughness and surface hardness. A grey relation grade obtained from the grey relation analysis is used to solve the EDM process with multiple performance characteristics. Experimental results have shown that electric discharge machining process performance can be improved efficiently through this approach. It is found that copper tungsten PM electrode gives better multi-objective performance than conventional copper electrode.